Altered functional connectivity in binge eating disorder and bulimia nervosa: A resting-state fMRI study - Stopyra, Marion A.; Simon, Joe J.; Skunde, Mandy; Walther, Stephan; Bendszus, Martin; Herzog, Wolfgang; Friederich, Hans-Christoph (Brain and behavior, 2019)
Introduction: The etiology of bulimic-type eating (BTE) disorders such as binge eating disorder (BED) and bulimia nervosa (BN) is still largely unknown. Brain networks subserving the processing of rewards, emotions, and cognitive control seem to play a crucial role in the development and maintenance of eating disorders. Therefore, further investigations into the neurobiological underpinnings are needed to discern abnormal connectivity patterns in BTE disorders. Methods: The present study aimed to investigate functional as well as seed-based connectivity within well-defined brain networks. Twenty-seven individuals with BED, 29 individuals with BN, 28 overweight, and 30 normal-weight control participants matched by age, gender, and education underwent resting-state functional magnetic resonance imaging. Functional connectivity was assessed by spatial group independent component analysis and a seed-based correlation approach by examining the default mode network (DMN), salience network (SN), and executive network (EN). Results: Group comparisons revealed that BTE disorder patients exhibit aberrant functional connectivity in the dorsal anterior cingulate cortex (dACC) within the SN, as well as in the medial prefrontal cortex within the DMN. Furthermore, BED and BN groups differed from each other in functional connectivity within each network. Seed-based correlational analysis revealed stronger synchronous dACC-retrosplenial cortex activity in the BN group. Conclusion: Our findings demonstrate abnormalities in brain networks involved in salience attribution, self-referential processing, and cognitive control in bulimic-type eating disorders. Together with our observation of functional connectivity differences between BED and BN, this study offers a differentiated account of both similarities and differences regarding brain connectivity in BED and BN.